Nitrogen Implanted α-SiC : A Correlation Between Electrical (C-V) Measurements and Damage Studies Using the Channeling Technique. - Chan, Albert M. C. (My University, 1975)
The annealing behaviour of 15N implanted, aluminum doped-SiC has been studied by measuring the differential capacitance as a function of applied bias. The samples were doubly implanted at 450°c with 45 Kev and 25 Kev ions, for a dose of 10^16/cm^2 at each energy.
An n-i-p structure with a thick insulator region was found after annealing at 1000°c. The thickness of this i region could be substantially reduced with additional annealing at higher temperatures, and a fairly good n-p junction was obtained after 1480°c anneal.
About 20-30% of the implanted nitrogen ions were found to be electrically active.
The C-V behaviour was found to have large variations with the a.c. measuring frequency.
Part A of two Project Reports; Part B can be found at: http://hdl.handle.net/11375/17691
Keywords: SiC, implanted, annealing, nitrogen, electrically, C-V